Uma investigação funcionalista do marcador discursivo então no estabelecimento de relações retóricas em elocuções formais do português - Alves, Deise Vieira dos Santos (2013)
This study aimed to investigate the performance of the discourse marker (DM) então in the establishment of relationships in formal speeches in Brazilian Portuguese. This research was based on functionalist assumptions of Rhetorical Structure Theory (RST), descriptive theory which aims to study the relationships established between parts of a text, and also on Textual-Interactive Grammar. The research corpus consisted of five formal utterances of the type classes of the Database of Funcpar (Functionalist Research Group of North/Northwest of Paraná). The formal utterances were transcribed according to the pattern established by NURC (Rio de Janeiro Oral Polite Norms Project) and segmented into intonation units (CHAFE, 1987). After the corpus analysis, it was ascertained that the DM então can sign more important units from a discursive topic or mark succession, acting in the establishment of different rhetorical relations. When the item marks important units from a topic, it can act in the ideational level, signaling elaboration, result and contrast relationships; in the propositional level, signalingconclusion, interpretation and evaluation relationships; in the speech-acts level, signaling preparation and motivation relationships; in topic structure level, signaling same-unit and parenthetical relationships.When the DM marks succession, it can mark idea succession, signaling sequence relationship; or action succession, signaling solutionhood, summary, restatement and multinuclear restatement. The research demonstrated that, although então is considered a basically sequencer DM, it can also act in the pragmatic level, establishing preparation relationship; and in the turn of talk dynamics, marking questions and answers by the solutionhood relationship. It was also observed that the DM então can act in the micro and macrostructure of the text.